PERANCANGAN GEDUNG SERBA GUNA UNIVERSITAS PALANGKA RAYA DENGAN PENDEKATAN ARSITEKTUR BIOFILIK - Muhammad Iqbal Maulana; Wijanarka Wijanarka; Theo Fransisco (Fakultas Teknik Universitas Palangka Raya, 2025)
Universitas Palangka Raya (UPR) has once again achieved notable progress in terms of growth and accomplishment of Key Performance Indicators (KPI), as set by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek). In 2024, UPR welcomed 3,400 new students through the Introduction to Campus Life for New Students (PKKMB) program. However, the university still faces limitations in infrastructure that support these expanding activities. A multipurpose building presents a strategic solution to this issue. Such a facility can function as a hub for academic events (seminars, graduations, student admissions, etc.), serving as a space for learning and interaction among students and faculty. Additionally, it can accommodate non-academic activities (events, job fairs, weddings, etc.), offering economic and business value while providing an open and flexible space for the community.